Comparative epidemiology of human metapneumovirus‐ and respiratory syncytial virus‐associated hospitalizations in Guatemala. Issue 4 (25th April 2014) - McCracken, John P.; Arvelo, Wences; Ortíz, José; Reyes, Lissette; Gray, Jennifer; Estevez, Alejandra; Castañeda, Oscar; Langley, Gayle; Lindblade, Kim A.
<x xml:space="preserve">Abstract</x> Background Human metapneumovirus (HMPV) is an important cause of acute respiratory infections (ARI), but little is known about how it compares with respiratory syncytial virus (RSV) in Central America. Objectives In this study, we describe hospitalized cases of HMPV‐ and RSV‐ARI in Guatemala. Methods We conducted surveillance at three hospitals (November 2007–December 2012) and tested nasopharyngeal and oropharyngeal swab specimens for HMPV and RSV using real‐time reverse transcription‐polymerase chain reaction. We calculated incidence rates, and compared the epidemiology and outcomes of HMPV‐positive versus RSV‐positive and RSV‐HMPV‐negative cases. Results We enrolled and tested specimens from 6288 ARI cases; 596 (9%) were HMPV‐positive and 1485 (24%) were RSV‐positive. We observed a seasonal pattern of RSV but not HMPV. The proportion HMPV‐positive was low (3%) and RSV‐positive high (41%) for age <1 month, whereas these proportions were similar (~20%) by age 2 years. The annual incidence of hospitalized HMPV‐ARI was 102/100 000 children aged <5 years [95% confidence interval (CI): 75–178], 2·6/100 000 persons aged 5–17 years (95%CI: 1·2–5·0), and 2·6/100 000 persons aged ≥18 years (95%CI: 1·5–4·9). Among children aged <5 years, HMPV‐positive cases were less severe than HMPV‐RSV‐negative cases after adjustment for confounders [odds ratio (OR) for intensive care = 0·63, 95% CI 0·47–0·84]; OR for death = 0·46, 95% CI 0·23–0·92). Conclusions Human metapneumovirus is a substantial contributor to ARI hospitalization in Guatemala, but HMPV hospitalizations are less frequent than RSV and, in young children, less severe than other etiologies. Preventive interventions should take into account the wide variation in incidence by age and unpredictable timing of incidence peaks.